(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2022)
This article is devoted to the determinants of corruption-related crimes and their prevention. Reducing the level of corruption and limiting it, first of all, solving the existing conditions and problems for its emergence.The most correct and effective way to fight against corruption is to identify the conditions and factors that create an opportunity for corruption in society and to eliminate them.